Circulating Fascin 1 as a Promising Prognostic Marker in Adrenocortical Cancer - Cantini, Giulia; Fei, Laura; Canu, Letizia; De Filpo, Giuseppina; Ercolino, Tonino; Nesi, Gabriella; Mannelli, Massimo; Luconi, Michaela (Frontiers in Endocrinology, 2021)
Fascin-1 (FSCN1) is an actin-bundling protein associated with an invasive and aggressive phenotype of several solid carcinomas, as it is involved in cell cytoskeleton rearrangement and filopodia formation. Adrenocortical carcinoma (ACC) is a rare endocrine malignancy characterized by poor prognosis, particularly when metastatic at diagnosis. Radical resection is the only therapeutic option for ACC patients in addition to the adjuvant treatment with mitotane. Novel specific biomarkers suggestive of tumor progression to refine diagnosis and prognosis of patients with advanced ACC are urgently needed. ACC intratumoral FSCN1 has previously been suggested as a valid prognostic marker. In the present study, we identified FSCN1 in the bloodstream of a small cohort of ACC patients (n=27), through a specific ELISA assay for human FSCN1. FSCN1 can be detected in serum and its circulating levels evaluated in pre-surgery samples resulted significantly higher in ACC patients from stage I/II and stage III/IV compared to nontumoral healthy controls (HC, n=4), FI: 5.5±0.8, P<0.001 and 8.0±0.5, P<0.001 for stage I/II and stage III/IV group vs HC, respectively. In particular, FSCN1 levels were significantly higher in advanced stage versus stage I/II (22.8±1.1 vs 15.8±1.8 ng/ml, P<0.005, respectively). Interestingly, circulating levels of pre-surgical FSCN1 can significantly predict tumor progression/recurrence (Log Rank=0.013), but not overall survival (Log Rang=0.317), in patients stratified in high/low PreS FSCN1. In conclusion, these findings - though very preliminary - suggest that circulating FSCN1 may represent a new minimally-invasive prognostic marker in advanced ACC, in particular when measured before surgery enables histological diagnosis.